2022
DOI: 10.3390/arm90040046
|View full text |Cite
|
Sign up to set email alerts
|

Awake Prone-Positioning in Patients on Non-Invasive Ventilation for Management of SARS-CoV-2 Pneumonia: A Systematic Review

Abstract: Introduction: Patients with corona virus disease-19 (COVID-19)-induced acute hypoxemic respiratory failure (AHRF) are often on non-invasive ventilation (NIV) and use of awake prone positioning (PP) may pose concern in terms of feasibility, efficacy and side effects. This systematic review was undertaken to evaluate the feasibility and efficacy of awake PP along with NIV in them. Materials and Methods: A systematic literature search was conducted from the inception of COVID-19 until 15 August 2021. Various fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Finally, we assessed 28 records in full text in the qualitative synthesis (Table 1). (1,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) Afterwards, 17 articles remained for the meta-analysis, of which 10 were observational studies, 4 were RCTs and 3 were non-RCTs (Figure 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we assessed 28 records in full text in the qualitative synthesis (Table 1). (1,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) Afterwards, 17 articles remained for the meta-analysis, of which 10 were observational studies, 4 were RCTs and 3 were non-RCTs (Figure 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…However, it is impossible to draw definitive conclusions because most of the studies that were included in these reviews did not have a comparison group. ( 26 , 28 ) Other studies showed an improvement in oxygen saturation (SpO 2 ) and the ratio of partial pressure of oxygen to the fraction of inspiratory oxygen (PaO 2 /FiO 2 ) but no apparent improvement in clinical outcomes, such as intubation and mortality. ( 11 , 15 , 29 , 30 )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-invasive ventilation (NIV) is a method of oxygenation supply that utilizes various interfaces such as a total face mask, nasal mask, helmet, nasal pillows, and oral mask, eliminating the need for an endotracheal airway ( 1 ). It is considered an effective treatment for various pulmonary diseases ( 2 , 3 ) and acute hypercapnic respiratory failure, such as chronic obstructive pulmonary disease (COPD) exacerbation ( 4 ).…”
Section: Introductionmentioning
confidence: 99%